The League of Nations and the Refugees from Nazi Germany : James G. McDonald and Hitler's Victims - Burgess, Greg 1957- (Bloomsbury Academic, 2016)
Greg Burgess’s important new study explores the short life of the High Commission for Refugees (Jewish and Other) Coming from Germany, from its creation by the League of Nations in October 1933 to the resignation of High Commissioner, James G. McDonald, in December 1935.The book relates the history of the first stage of refugees from Germany through the prism of McDonald and the High Commission. It analyses the factors that shaped the Commission’s formation, the undertakings the Commission embarked upon and its eventual failure owing to external complications.The League of Nations and the Refugees from Nazi Germany argues that, in spite of the Commission’s failure, the refugees from Nazi Germany and the High Commission’s work mark a turn in conceptions of international humanitarian responsibilities when a state defies standards of proper behaviour towards its citizens